Accounting Information System at the Indonesian Architects Association of North Sumatra Province Using the Cash Basis Method - Yudi Lizardi Mahna Siregar; Raissa Amanda Putri; Imam Adlin Sinaga (Jurnal Info Sains : Informatika dan Sains, 2023)
The Indonesian Architects Association (IAI) of North Sumatra Province, is an organization engaged in the field of architecture and has an office in Medan. So far, the recording of all data and financial transactions is still done manually, processed based on the accounting cycle by handwriting and is difficult to find when preparing reports, so that preparing the financial reports needed by the organization will take a long time. The purpose of this study was to design and build an accounting information system at the Association of Indonesian Architects in North Sumatra Province. The research method used in this study is a qualitative approach. The method used in developing this application is the waterfall method, and for its design, the laravel framework was used along with programming languages such as PHP, HTML, JavaScript, and CSS. The database used is MySQL. The accounting method used is the cash basis method. The system is tested using black box testing. While the Unified Modelling Language (UML) is used as the modelling languange for software development. The implementation of this accounting information system is expected to improve the transparency of financial management, facilitate faster decision-making, and produce accurate financial reports.